ANALISIS PENGARUH PERTUMBUHAN PDB, INFLASI DAN BI RATE TERHADAP NON PERFORMING LOAN BANK YANG TERDAFTAR - Ricky Talumantak (Panorama Nusantara, 2020)
This research empirically studies several macroeconomic factors determining the non-performing loans (NPL) of the banking which listed at Indonesia Stock Exchange. This research employ three macroeconomic variables influencing the NPL such as GDP growth, Inflation and BI (Bank Indonesia) rate as proxy of interest rate on yearly basis from 2010 to 2019. Multiple regression analysis method was deployed to discover the significant relationships between the macroeconomic variables and NPL. Empirical results provide evidence that GDP growth, Inflation and BI rate individually are significant and negatively relationship with NPL. This research also find that GDP growth, Inflation and BI rate simultaneously have significant relationship to NPL.